1996
DOI: 10.1017/s002221510013292x
|View full text |Cite
|
Sign up to set email alerts
|

Client centred hypnotherapy in the management of tinnitus – is it better than counselling?

Abstract: The aim of this study was to assess whether client centred hypnotherapy (CCH) which required three sessions with a trained therapist was superior to a single counselling session in reducing the impact of tinnitus.Patients were randomly allocated to receive either counselling (n = 42) or CCH (n = 44). The outcome measures were: tinnitus loudness match, subjective tinnitus symptom severity score, trend of linear analogue scale, request for further therapy and whether the patient had an impression of improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Mason et al 74 found hypnosis superior to counseling (global improvement 46% vs. 14%), but patients in the hypnosis group received individual therapy in three sessions while the control group had only a single group counseling session. Thus it is difficult to conclude that the outcome difference was due to hypnosis rather than simply the intensity of clinical interaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mason et al 74 found hypnosis superior to counseling (global improvement 46% vs. 14%), but patients in the hypnosis group received individual therapy in three sessions while the control group had only a single group counseling session. Thus it is difficult to conclude that the outcome difference was due to hypnosis rather than simply the intensity of clinical interaction.…”
Section: Resultsmentioning
confidence: 99%
“…This review will consider only RCTs in which psychotherapy or counseling was a defined treatment arm compared with other forms of treatment or other forms of psychotherapy. Three such comparisons have already been discussed, none finding advantage for psychotherapy when compared with masking 58 or hypnosis 56,74 . Psychotherapy (cognitive‐behavioral‐coping) has also been compared with yoga; 76 each group received 20 hours of therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen types of psychological therapy have been tested in an RCT. These 14 were comprised of more traditional second-wave CBT including face-to-face CBT ( Kröner-Herwig et al 1995 , 2003; Zachriat & Kröner-Herwig 2004 ; Andersson et al 2005 ; Robinson et al 2008 ; Tucker 2013 ), internet-delivered CBT ( Andersson et al 2002 ; Kaldo et al 2008 ; Abbott et al 2009 ; Hesser et al 2012 ; Nyenhuis et al 2013 ; Jasper et al 2014 ), group CBT ( Kaldo et al 2008 ; Nyenhuis et al 2013 ; Jasper et al 2014 ), bibliotherapy CBT ( Kaldo et al 2007 ; Nyenhuis et al 2013 ), stepped care CBT ( Cima et al 2012 ), group cognitive therapy ( Jakes et al 1992 ), behavior therapy ( Lindberg 1988 ; Lindberg et al 1988 ); ACT ( Westin et al 2011 ); internet-delivered ACT ( Hesser et al 2012 ); mindfulness ( Kreuzer et al 2012 ); tinnitus education ( Mason et al 1996 ; Kröner-Herwig et al 2003 ; Henry et al 2007 ; Tucker 2013 ; Argstatter et al 2015 ), tinnitus education with cognitive therapy ( Henry & Wilson 1996 ), attention control, imagery training, and cognitive restructuring ( Henry & Wilson 1998 ), and relaxation and distraction ( Kröner-Herwig et al 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study found hypnosis to be no better than counseling, and one study found that the nonresponders to hypnotherapy were the patients with the worst hearing losses. 47–50 …”
Section: Discussionmentioning
confidence: 99%